MENJADIKAN ANRI SEBAGAI LEMBAGA KEARSIPAN KELAS DUNIA MELALUI KINERJA PENGELOLAAN ARSIP STATIS: Array - Azmi Azmi (Arsip Nasional Republik Indonesia, 2014)
Archives is a source of information and the collective memory of a nation. Through archives can be learned about the history of failures that have been experienced and accomplishments ever achieved by the nation, so it can be used as a reference for the future development of the nation. The National Archives of the Republic of Indonesia (ANRI) is mandated by Law No. 43 of 2009 on Records and Archives Administration to carry out the management of national archives received from state agencies, companies, political organizations, social organizations, and individuals. ANRI existence as archival institutions in an effort to manage the data factual history of the nation can be a therapeutic medium for rescue andpreservation of the national and international collective memory.The collection of archives in ANRI is a national asset and collective memory of the nation that has important historical value over administration of society, nation and state. With a number of great and variety of the collection of archives of course it becomes a strength and opportunity for ANRI to be authoritative archival institutions in the world. ANRI performance in managing archives as a source of knowledge and collective memory of nation can be used by the national and international community is strongly influenced by the model of archives management system implemented. For making ANRI as a world-class archival institutions affected by the performance of ANRI in the management of archives. Therefore, ANRI should make the strategy through implemented a comprehensive archival management system and integrated with strengthening policies, development of archives management system, improvement of archival resources and strengthening synergies.